2019
DOI: 10.21203/rs.2.12038/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Antifungal Susceptibility of Candida albicans Causing Vaginal discharge Among Pregnant Women in Lebanon

Abstract: Background: Vaginal candidiasis is frequently prevalent in pregnant women and is associated with sepsis and adverse neonatal outcomes. This study determined the presence of Candida species in symptomatic pregnant women and evaluated the antifungal susceptibility profile of the isolated strains. It also aimed to explore whether Candida species predicts gestational complications and adverse neonatal outcomes. Methods: A total of 258 pregnant women at 35 to 37 week of gestation participated in this study. Vaginal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
(26 reference statements)
1
4
2
Order By: Relevance
“…In Greece, the antifungal susceptibility profile has shown that Candida isolates from patients with vulvovaginal candidiasis to AMB and VRC were 0.2% and 1.4%, respectively [36]. In addition, Ghaddar et al revealed that 97.5% of C. albicans isolates from VVC patients were resistant to VRC [37]. Our findings demonstrated that 23.4% and 10.6% of C. albicans isolates were resistant to FLC and ITC, respectively.…”
Section: Discussionsupporting
confidence: 53%
“…In Greece, the antifungal susceptibility profile has shown that Candida isolates from patients with vulvovaginal candidiasis to AMB and VRC were 0.2% and 1.4%, respectively [36]. In addition, Ghaddar et al revealed that 97.5% of C. albicans isolates from VVC patients were resistant to VRC [37]. Our findings demonstrated that 23.4% and 10.6% of C. albicans isolates were resistant to FLC and ITC, respectively.…”
Section: Discussionsupporting
confidence: 53%
“…In the current study, the prevalence rate of vulvovaginal candidiasis was 33.53% between participated pregnant women. This result is lower than that reported in Lebanon (39%), 7 Pakistan (38%), 6 and India (42.37%). 23 However, another study reported a lower prevalence rate (29%) of VVC in Iraq.…”
Section: Phylogenetic Analysiscontrasting
confidence: 66%
“…It can also be found that the high occurrence rate of C. albicans could be due to increased physiological changes, estrogen, and rich glycogen content of the vaginal mucosa, thereby providing an adequate supply of utilizable sugar that favor its growth during pregnancy. 14 However, Ghaddar et al 7 reported a low incidence of C. albicans (42%) comparing to non-albicans Candida species (58%), where include C. glabrata and C. krusei. Molecular subtyping of C. albicans provides a useful tool for studying the epidemiology of this commonly causative agent of candidiasis in humans for identification of pathogenic subpopulation within this species, thereby assist in developing appropriate therapeutic strategies to combat the disease.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, C. albicans infections pose a serious public health threat worldwide including Lebanon. To date only a handful of studies have addressed resistance of Lebanese C. albicans isolates to azoles, echinocandins, and polyenes [11][12][13][14][15][16][17] but none of the studies have looked at the entire genome of C. albicans to generate a complete picture of the genomic aspects of antifungal resistance.…”
Section: Introductionmentioning
confidence: 99%